Proceso de atención de enfermería basado en la teoría de Virginia Henderson en síndrome epiléptico asociado a preeclampsia - Valladolid Yaguana, Leidy Elizabeth; Veas Sanchez, Ingrid Geomar (Machala : Universidad Técnica de Machala, 2022)
Introduction: Epileptic episodes in a pregnant woman are a risk factor for developing preeclampsia in pregnancy that could cause congenital malformations, maternal deaths and neurological damage in the newborn including the mother, therefore promotion and prevention is essential to be able to detect any abnormality and follow-up so that the pregnancy is a success. Nursing provides individualized and humanized care to the patient, fulfilling a very important role in the prevention of diseases in the promotion and promotion of health. Virginia Henderson's model is based on 14 fundamental needs in the human being, it allows to include biopsychosocial elements in order to improve the quality of life and promote self-care where individuals are capable of making their own decisions with autonomy and feel capable of performing their own purposes. The clinical case study based on the Virginia Henderson Theory in epileptic syndrome associated with preeclampsia, because this disease represents a problem worldwide, manifested by the increase in blood pressure values greater than 130/90 mmhg, this disease It is more prevalent in pregnant women, presenting after 20 weeks of pregnancy, which can have repercussions for the mother as well as for the fetus. Objective: The present case analysis has the general objective of applying the process of nursing care based on Virginia Henderson's theory through a case study of epileptic syndrome associated with preeclampsia, allowing us to improve their quality of life. Methodology: This case analysis is of a qualitative type because information was collected through observation and review of the clinical history, which allowed us to investigate and investigate scientific databases.
Introducción: Los episodios epilépticos en una gestante son un factor de riesgo para desarrollar preeclampsia en el embarazo que podrían ocasionar malformaciones congénitas, muertes maternas y daños neurológicos en el recién nacido incluido a la madre por ello la promoción y prevención es esencial para poder detectar alguna anomalía y realizar el seguimiento para que el embarazo sea un éxito. Enfermería brinda cuidados individualizados y humanizados al paciente, cumpliendo un rol muy importante en la prevención de enfermedades en el fomento y promoción de la salud. El modelo de Virginia Henderson se basa en 14 necesidades fundamentales en el ser humano, permite englobar elementos biopsicosociales para así poder mejorar la calidad de vida y fomentar el autocuidado donde los individuos sean capaces de tomar sus propias decisiones con autonomía y se sienta capaz de realizar sus propios propósitos. El estudio de caso clínico es basado en la Teoría de Virginia Henderson en síndrome epiléptico asociado a preeclampsia, debido a que esta enfermedad representa un problema a nivel mundial, manifestado por el aumento de los valores de presión arterial mayor a 130/90 mmhg, esta enfermedad es más prevalente en mujeres que se encuentran en estado de gestación, presentándose a partir de las 20 semanas de embarazo lo cual puede traer repercusiones para la madre como para el feto.
Keywords: PREECLAMPSIA; SINDROME EPILEPTICO; VIRGINIA HENDERSON